Audit Operasional untuk Mengukur Efektivitas dan Efisiensi Pengelolaan Investasi Pada Dana Pensiun INTI - Fitria Amelia Kurniawan; Yanti Rufaedah; Dian Imanina Burhany (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study aims to determine the implementation of operational audits and measure the effectiveness and efficiency of investment management at the INTI Pension Fund. The research method is a qualitative descriptive method with data collection techniques carried out, namely documentation, interviews and observation techniques. Through this study, the authors conducted an operational audit with secondary data in the form of Investment Reports and INTI Pension Fund Financial Statements that had been audited from 2016 to 2020. As a result of the operational audit show that investment management in the INTI Pension Fund is in accordance with the Investment Directive, but still has several weaknesses. It can be concluded that investment management has not been effective in 2018-2020 because the rate of return on investment or ROI has not reached the target set in the Investment Direction, which is 7.43%, 6.68% and 7.68% while it should be 9%.